Synthesis of cross-conjugated trienes by rhodium-catalyzed dimerization of monosubstituted allenes - Miura, Tomoya; Biyajima, Tsuneaki; Toyoshima, Takeharu; Murakami, Masahiro (Beilstein Journal of Organic Chemistry, 2011)
A rhodium(I)/dppe catalyst promoted dimerization of monosubstituted allenes in a stereoselective manner to give cross-conjugated trienes, which are different from those obtained by a palladium catalyst.
Keywords: allene; cross-conjugated triene; dimerization; rhodium; stereoselective